Grooming Konselor Muslim: Panduan Berpenampilan dalam Kitab Asy-Syama’il Al-Muhammadiyah (Jurusan Bimbingan dan Konseling Islam, 2020)
The Prophet Muhammad is a role model for all Muslims in all parts of the world. Of course,imitating one's morals is a special priority for a Muslim adviser and can appreciate and reap blessings. Thepurpose of this research is to find a description of the care of Muslim counselors through a study of the habits ofthe appearance of the Prophet Muhammad in the book Asy-Shama'il Al-Muhammadiyah. This researchmethod uses qualitative studies through library research (content research) with content analysis techniques andtriangulation of data sources. The results found that Muslim care could be copied from the habits of theappearance of the Prophet Muhammad. While Muslim grooming can imitate (highlight) the shape of hair,turban (songkok), clothing, gloves, sandals (sandals), rings and fragrances seen by the Prophet Muhammad.This research can be useful for Muslims in managing their appearance (or care) in talking with counselees and/ or in providing counseling guidance services.